PENGARUH DESENTRALISASI FISKAL DAN PERTUMBUHAN EKONOMI SERTA BELANJA MODAL TERHADAP INDEKS PEMBANGUNAN MANUSIA (STUDI KASUS 9 KOTA DI PROVINSI JAWA TIMUR TAHUN 2008 - 2017) - Setiawan, Moch. Rudy; arif, syamsul (Fakultas Ekonomi Universitas 17 Agustus 1945 Surabaya, Indonesia, 2019)
The prosperity of society is measured by the HDI (Human Development Index), so in order to improve people's health, it is necessary to use the Regional Budget (APBD) optimally and efficiently. The allocation of the APBD as an instrument aims at the economic development in addition to human development. This study analyzes the influence of fiscal decentralization, economic growth, and capital expenditure on the human development index of nine cities in East Java Province 2008-2017. This research uses panel data by using the Fixed Effect Model regression method which is processed by requiring Eviews 9, from the results of data processing showing that fiscal decentralization, economic growth, and capital expenditure have a partial significant and positive effect on the human development index of nine cities in East Java 2008 -2017.